Pembatalan UU BHP dan Pendidikan Berbasis Humanistik - Abdul Wahid (The Constitutional Court of the Republic of Indonesia, 2010)
Mahkamah Konstitusi (MK) has postponed the Constitution (UU) Number 9 Year 2009 dealing with Educational Law Institutions (BHP) since it is evaluated violating UUD 1945. MK evaluates that this UU BHP is against the UUD 1945 so that any expectations from the people expect it should be brought on. UU BHP inspite of uniforming the form of educational law institutions so that it ignores the form of any other law intituions such as private organization, waqaf, and so forth, also gives the justification to the commercialism practices and education capitalism, which dangerously cause the threatened human rights of poor people in gaining proper education or humanity.